Dynamic Loading Research of the Gondola car Supporting Structure with an Elastic-Viscous Filler in a Center Sill - Lovska, A. O; Fomin, O. V; Rybin, A. V (Science and Transport Progress, 2021)
Purpose. The work aims to investigate dynamic loading of the supporting structure of a gondola car with an elastic-viscous filler in the center sill by means of mathematical modeling. Methodology. Mathematical modeling of the dynamic loading of the supporting structure of a gondola car with a closed center sill filled with a filler with elastic-viscous properties has been carried out. The case of the highest load on the supporting structure of the gondola car in operation is taken into account – a shunting collision, taking into account the action of a load of 3.5 MN on the rear stop of the automatic coupler. To determine the dynamic loading of a gondola car, a mathematical model formed by prof. G. I. Bohomaz was used. However, within the framework of this study, the model was refined by adapting it to the determination of the dynamic loading of a gondola car. It also takes into account the friction forces arising between the center plates of the body and the center pivots of the bogies, as well as the properties of the energy-absorbing material. The solution of the mathematical model was carried out in the MathCad software package. In this case, the differential equations of motion were reduced to the Cauchy normal form, and then integrated using the Runge-Kutta method. Initial displacements and speeds are taken equal to zero. The calculation was carried out on the example of a universal gondola car model 12-757 built by Kriukivskyi Carriage Works PJSC (Kremenchug) on standard bogies 18-100. Findings. Accelerations are obtained as components of a dynamic load acting on a gondola car with a closed center sill structure filled with an elastic-viscous filler. It was found that with the stiffness of the center sill filler of 82 kN/m, as well as the viscous resistance coefficient of -120 kN∙s/m, the maximum accelerations of the gondola car supporting structure is about 37 m/s2 (0.37g). Originality. A mathematical model is proposed for determining the dynamic loading of a gondola car with a closed structure of a center sill filled with an elastic-viscous filler. The model makes it possible to obtain accelerations as the components of the dynamic loading acting on the supporting structure of the gondola car, taking into account the improvement measures during a shunting collision. Practical value. The results of the research will help to reduce the damage to the supporting structures of gondola cars in operation, reduce the cost of their maintenance, create developments in the design of innovative structures of rolling stock, as well as increase the efficiency of its operation.